Seasonality of respiratory viruses causing hospitalizations for acute respiratory infections in children in Nha Trang, Vietnam. (October 2018) - Althouse, Benjamin M; Flasche, Stefan; Minh, Le Nhat; Thiem, Vu Dinh; Hashizume, Masahiro; Ariyoshi, Koya; Anh, Dang Duc; Rodgers, Gail L.; Klugman, Keith P.; Hu, Hao; Yoshida, Lay-Myint
Highlights: Hospitalizations for respiratory viruses are seasonal in Vietnam Respiratory syncytial virus peaks in the late summer months, and inuenza A in April to June No clear seasonality is seen for human rhinovirus Human parainuenza 3 and human rhinovirus are positively associated with dew point This work can inform the timing of inuenza and RSV vaccination and the judicious use of antibiotics in Vietnam Abstract: Background: Acute respiratory infections (ARIs) are the most common causes of death in children under 5 years of age. While the etiology of most pneumonia and ARI episodes is undiagnosed, a broad range of ARI-causing viruses circulate widely in South East Asia. However, the patterns and drivers of the seasonal transmission dynamics are largely unknown. Here we identify the seasonal patterns of multiple circulating viruses associated with hospitalizations for ARIs in Nha Trang, Vietnam. Methods: Hospital based enhanced surveillance of childhood ARI is ongoing at Khanh Hoa General Hospital in Nha Trang. RT-PCR was performed to detect 13 respiratory viruses in nasopharyngeal samples from enrolled patients. Seasonal patterns of childhood ARI hospital admissions of various viruses were assessed, as well as their association with rainfall, temperature, and dew point. Results: Respiratory syncytial virus peaks in the late summer months, and influenza A in April to June. We find significant associations between detection of human parainfluenza 3 and human rhinovirus with the month's mean dew point. Using a cross-wavelet transform we find a significant out-of-phase relationship between human parainfluenza 3 and temperature and dew point. Conclusions: Our results are important for understanding the temporal risk associated with circulating pathogens in Southern Central Vietnam. Specifically, our results can inform timing of routing seasonal influenza vaccination and for when observed respiratory illness is likely viral, leading to judicious use of antibiotics in the region.